THE ART OF MUSIC AS A MEANS OF EXPRESSION ELEVATING THE HUMAN SPIRITUAL REALM - Sarvinozxon Olimova (International Journal of Literature and Language Studies, 2026)
This article examines the role and expressive means of the art of music in elevating the spiritual and psychological realm of human beings and in aesthetic education. It analyzes the social and psychological essence of artistic creation, mechanisms of musical perception, listener culture, and the interconnection between composer and performer skills. Additionally, priority directions of state policy aimed at developing music education and upbringing in our country are addressed. The results of the article hold practical and theoretical significance in the fields of music pedagogy, psychology of art, and cultural studies.